Pendidikan Jasmani: Memperhatikan Kesehatan, Gizi, Tidur dan Kebersihan - Filzah Azkia Nasution; Maharami Nur Annisaa Siregar (STIKes Ibnu Sina Ajibarang, 2025)
This article examines physical education from the perspective of Hadith Tarbawi, highlighting the importance of maintaining physical health, nutrition, sleep, and cleanliness as integral components of Islamic education. The study explains how various prophetic traditions emphasize strength, discipline, moral integrity, and healthy living as characteristics of a strong Muslim. Sports such as running, swimming, archery, and horseback riding-practiced or encouraged by the Prophet-serve as foundations for building physical fitness and mental resilience. This article also explores the implementation of hadith values within physical education, including honesty, cooperation, discipline, and caring for the environment. These principles reinforce the holistic nature of Islamic education, in which physical, spiritual, and moral development are interconnected. The findings indicate that physical education in Islamic perspective not only strengthens the body but also shapes strong character and supports the optimal performance of religious duties.